2023
DOI: 10.3390/jcm12103597
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Fertility and Pain after Endometriosis Resection and Adhesion Prevention with 4DryField® PH: Follow-up of a Randomized Controlled Clinical Trial

Abstract: Background: Adhesions after endometriosis resection are frequent and the most common causes for chronic pain and secondary infertility. Primary results of our randomized controlled trial (RCT) on adhesion prevention after deep infiltrating endometriosis (DIE) resection using the gel barrier 4DryField® PH showed 85% adhesion reduction in second-look surgeries. Secondary endpoint data on fertility and pain development were collected during 12-month follow-ups. Methods: This RCT comprised 50 patients. Preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The authors used 4DF in 25 patients and found a reduction of adhesions by 85% compared to 25 controls. A recent follow-up analysis of the same cohort showed positive results regarding fertility outcomes and pain reduction in the study group ( Krämer et al, 2023 ).…”
Section: Discussionmentioning
confidence: 89%
“…The authors used 4DF in 25 patients and found a reduction of adhesions by 85% compared to 25 controls. A recent follow-up analysis of the same cohort showed positive results regarding fertility outcomes and pain reduction in the study group ( Krämer et al, 2023 ).…”
Section: Discussionmentioning
confidence: 89%
“…A novel adhesion barrier powder made from purified potato starch has been found to effectively reduce adhesion severity and extent by 85% compared to saline solution irrigation after endometriosis surgery, as confirmed by a second-look laparoscopy [178]. After 12 months of follow-up, the pregnancy rate in the intervention group was significantly higher than that in the control group, and the cycle-independent pelvic pain and dysmenorrhea were improved in the intervention group [179]. One limitation of this study is that the researchers did not evaluate the changes in OR markers before and after treatment.…”
Section: Hyperactivation Of Primordial Folliclementioning
confidence: 88%